Transforsactional leadership's effectiveness in reducing turnover in the Malaysian hospitality industry - Tan, Jin Aun (2023)
Turnover is a very big problem for the hospitality industry compared to many other industries and this has a cascading effect on profitability and service standards. As hospitality is a labour intensive industry, ways and means to reduce turnover has been a focus of research. The transformational and transactional leadership style has played a role in employee turnover intention but this research paper seeks to explore a combination of both leaderships styles, utilising the benefits of both styles to address the issue of employee turnover intention.